Age-Stratified Outcomes of Mehta Casting in Idiopathic Early-Onset Scoliosis: A Multicenter Review. (16th November 2022) - Fedorak, Graham T.; MacWilliams, Bruce A.; Stasikelis, Peter; Szczodry, Michal; Lerman, Joel; Pahys, Joshua M.; D'Astous, Jacques
Abstract : Background: This study provides age-stratified outcomes of cast treatment for idiopathic early-onset scoliosis. Methods: This is a multicenter, retrospective review of patients with idiopathic early-onset scoliosis treated with Mehta casting at 4 tertiary children's hospitals between 2001 and 2016. The inclusion criteria were idiopathic early-onset scoliosis and a minimum follow-up of 2 years after casting ended. The exclusion criteria were <2 casts, >3 casts at an outside facility, and a major curve of <20° pre-treatment. Subjects were grouped by age at first cast: <18 months, 18 to <24 months, 2 to <3 years, 3 to <4 years, and ≥4 years. Results: There were 134 patients with a mean follow-up of 5.2 years (95% confidence interval [CI], 4.8 to 5.5 years) after casting. Prior to treatment, the major curve was not significantly different between the various age groups and was a mean of 50.4° (95% CI, 48.0° to 52.8° [range, 22° to 109°]). Of the <18-month group (n = 59), at the final follow-up at a mean of 7.4 years (95% CI, 6.8 to 8.1 years) of age, 75% had scoliosis of <15°, and 6.8% had undergone a surgical procedure or had a major curve of ≥50°. The results declined in the 18 to <24-month group (n = 30), with a major curve of <15° at the final follow-up at 8.5 years (95% CI, 7.3 to 9.7 years) of age in 33% (p < 0.001), and 17% having undergone a surgical procedure or had a major curve of ≥50°, with results nearly identical in the 2 to <3-year group (n = 21). The results continued to decline with increasing age; 23% of the 3 to <4-year group had a major curve of <15° at the final follow-up, and 31% had undergone a surgical procedure or had scoliosis of ≥50°. Of the ≥4-year group, just 9.1% had scoliosis of <15° (p < 0.0001 compared with the <18-month group), and 64% had undergone a surgical procedure or had scoliosis of ≥50°. Conclusions: Children who underwent casting prior to 18 months of age were more likely to have a major curve of <15° at a minimum 2-year follow-up after casting. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.